TEM investigations of gate-all-around nanowire devices. (4th November 2019) - Favia, P; Richard, O; Eneman, G; Mertens, H; Arimura, H; Capogreco, E; Hikavyy, A; Witters, L; Kundu, P; Loo, R; Vancoille, E; Bender, H
Abstract: Vertically stacked gate-all-around nanowires (GAA NWs) are considered a promising architecture for ultimately scaled complementary metal oxide semiconductor devices. These are the natural evolution of the fin-shaped field effect transistor (finFET) design and enable a better electrostatic control and a higher drive current per footprint w.r.t. previous architectures. Transmission electron microscopy (TEM) analysis is employed in the development stages of these devices to investigate morphology, material diffusion, oxidation and strain in order to achieve the desired nanowires shape and size and the required performances. Nano beam diffraction and geometric phase analysis of high-resolution scanning TEM (STEM) images are used in this work to evaluate strain at the nm-scale along the nanowires at different steps of the fabrication process. Initially strained Ge layers, in the early stages of the GAA NWs fabrication, relax after the fin-reveal and source/drain etching process steps. Strain is then restored after source/drain epitaxial deposition and maintained till the NWs release. TEM analyses of these structures are particularly challenging due to the dimensions of the GAA NWs which are smaller than the thickness of a typical TEM specimen. This generates artifacts due to different materials and multiple structures overlapping in projection in TEM images. To avoid these issues, several TEM lamellae at different positions in the device and/or 3D imaging STEM/energy dispersive spectroscopy tomography are employed.